SIFAT FISIKA BAMBU PETUNG (Dendrocalamus asper (Schult. f.) Backer ex Heyne) dari KHDTK (Kawasan Hutan Dengan Tujuan Khusus) SENARU BERDASARKAN POSISI AKSIAL - Dwi Sukma Rini (Jurnal Belantara)
The aims of this study are to determine the influence of bamboo culm section, axial position, and interaction between the culm section and the axial position on physical properties of bamboo petung derived from KHDTK SENARU, North Lombok. The method used in this study was the experimental method using a completely randomized factorial design (CRFD) with two factor. The first factor was the culm section (node and internode) and the second factor was the axial position (bottom, middle and top). Parameters that were observed in this study were green moisture content (MC), air dried MC, green specific gravity, longitudinal and thick shrinkage from green condition to oven dried condition. Data analysis used is the analysis of variance with a confidence level of 95%. The result shows that culm section, the interaction between culm section and axial position did not give significant influence on physical properties. While the axial position which included green MC and green specific gravity has a significant influence on physical properties. A further test was done on a significant result using Tukey's HSD test. Green MC decreases along the culm from base to top. In contrast, green specific gravity increases along the culm from base to top.